PERILAKU IBU RUMAH TANGGA PEMAKAI KREDIT BARANG KELILING (MINDRING: STUDI KASUS PADA IBU RUMAH TANGGA PEMAKAI KREDIT BARANG KELILING MINDRING DI DUKUH PUNDUNG TEGAL SARI DESA MANJUNG KECAMATAN SAWIT KABUPATEN BOYOLALI) - Suryono, Anike Nurmalita Rizki Putri; Wijaya, Mahendra; Demartoto, Argyo (Jurnal Analisa Sosiologi, 2015)
The objective of research was to find out the behavioral pattern andimpact of housewives using mobile merchandise loan (mindring) in PundungTegal Sari Hamlet, Desa Manjung. This study employed a qualitativeapproach method with a single embedded case study. The data source wasobtained from informant, event and activity, document and archive. Thesampling technique used was purposive sampling one with maximumvariation sampling. The data collection was conducted using directobservation, interview, documentation and photographs. The data validationtest was carried out using source triangulation. Mindring activity among thehousewives was encouraged by inadequate cash ownership to buy the goods tofulfill the family’s personal and collective needs. In this case housewives were able to divide the money that had to obtain various goods and consumergoods. But with the easiness provided by the load of debt, indirectly creatingthe consumer behavior within a housewife. Based on consumer behavior, housewife always feel in need of goods is credited. Keywords: Behavior, Housewives, Mindring